Instructional Leadership: Its Role in Sustaining School Improvement in South African Schools - Shava, George. N.; Heystek, Jan; Chasara, Thompson (International Journal of Social Learning (IJSL), 2021)
Recent studies conducted around the world have revealed a clear link between the instructional position of principal leadership and school improvement. Instructional leadership, which aims to foster a teaching and learning community, is seen as a key component of successful teaching and long-term school improvement. The rise in site-specific management roles, which are based on instructional leadership experiences, is one of the initiatives launched by the South African government to reform education. In South Africa, school principals are responsible for academic development. This qualitative research aimed to learn more about the role of principals in sustaining school improvement in the North West Province of South Africa. Premised in the qualitative research approach, a purposive sampling technique was used to select six schools that had sustained school improvement for some years. Findings from the study revealed that principals play a crucial role in sustaining school improvement. The study findings reinforce recent literature that identifies instructional leadership as a cornerstone for school improvement.